PENGARUH PENERAPAN SISTEM E-FILING, TINGKAT PENDIDIKAN, DAN PENGETAHUAN PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK DENGAN BIAYA KEPATUHAN SEBAGAI VARIABEL MODERASI (Studi Empiris pada Wajib Pajak Orang Pribadi di KPP Pratama Pekanbaru Tampan - Sihite, Vorarta Adelia Kristauli; Nasrizal, Nasrizal; Safitri, Devi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2025)
This study aims to determine the effect of the implementation of E-filing, compliancelevel, and tax knowledge on taxpayer compliance with compliance costs as a moderatingvariable. The population in this study is individual taxpayers registered at KPP PratamaTampan Pekanbaru. The sampling method used in this study is non-probability sampling.The data analysis technique used in this study is analysis with the SEM SMARTPLSmodel. The results of the study showed that the variable Education Level had no effect ontaxpayer compliance, the variable of e-filing and tax knowledge had an effect on taxpayercompliance, compliance costs were not able to moderate the influence of Education Levelon taxpayer compliance, compliance costs were able to moderate the effect of theimplementation of e-filing and tax knowledge on taxpayer compliance.Keywords: Taxpayer Compliance, E-filing, Education Level, Taxation Knowledge